Changes in the prevalence of comorbidity in the Australian population with cancer, 2007–2014. (June 2018) - Ng, Huah Shin; Koczwara, Bogda; Roder, David; Vitry, Agnes
Highlights: Comorbidity is more prevalent in the cancer population than the general population. The prevalence of most comorbid conditions was fairly stable between 2007 and 2014. The prevalence of mental, endocrine and respiratory diseases has increased over time similarly in cancer and control groups. Abstract: Background: Coexistence of multiple chronic diseases is highly prevalent among the cancer population. This study aims to assess changes in the prevalence of chronic conditions among the population with cancer compared to the Australian general population between 2007 and 2014. Methods: Data from three successive National Health Surveys conducted by the Australian Bureau of Statistics between 2007 and 2014 were utilized. Comparisons were made between the samples of the Australian population aged 25 years and above with a history of cancer and those respondents who did not report having had a cancer using logistics regression models. Results: People with a history of cancer had significantly higher odds of reporting non-infectious comorbidity compared to the non-cancer groups across the three surveys. There were no significant changes in the prevalence of diseases affecting circulatory, musculoskeletal, digestive, nervous system, blood and blood forming organs, eye, skin and infectious and parasitic diseases over time among the population with cancer. The prevalence of mental and behavioural problems, endocrine, nutritional and metabolic diseases, and diseases of respiratory and genitourinary system has increased over time among the cancer survivors. Conclusion: Comorbidity is more prevalent among the cancer population than the general population without cancer. The prevalence of comorbidity was fairly stable for most but not all comorbidities in the population with cancer over the eight-year study period. Further studies on the impacts of coordinated care models for the management of multi-morbidity experienced by cancer survivors that align with the 'National Strategic Framework for Chronic Conditions' are needed.